The Role of Impulsivity and Reward Deficiency in “Liking” and “Wanting” of Potentially Problematic Behaviors and Substance Uses - Domonkos File; Beáta Bőthe; Bálint File; Zsolt Demetrovics; Zsolt Demetrovics (Frontiers in Psychiatry, 2022)
A few studies have examined the changes in substance- and behavior-related “wanting” and “liking” of human subjects, the key properties of Incentive Sensitization Theory (IST). The aim of this study was to examine the dissociation between “wanting” and “liking” as a function of usage frequency, intensity, and subjective severity in individuals across four substances (alcohol, nicotine, cannabis, and other drugs) and ten behaviors (gambling, overeating, gaming, pornography use, sex, social media use, Internet use, TV-series watching, shopping, and work). Also, the potential roles of impulsivity and reward deficiency were investigated in “wanting,” “liking,” and wellbeing. The sex differences between “wanting” and “liking” were also examined. Based on our findings using structural equation modeling with 749 participants (503 women, Mage = 35.7 years, SD = 11.84), who completed self-report questionnaires, “wanting” increased with the severity, frequency, and intensity of potentially problematic use, while “liking” did not change. Impulsivity positively predicted “wanting,” and “wanting” positively predicted problem uses/behaviors. Reward deficiency positively predicted problem uses/behaviors, and both impulsivity and problem uses/behaviors negatively predicted wellbeing. Finally, women showed higher levels of “wanting,” compared to men. These findings demonstrate the potential roles of incentive sensitization in both potentially problematic substance uses and behaviors.